Beginners Guide to the World Economy: Eighty One Basic Economic Concepts That Will Change the Way You See the World - Randy Charles Epping (Vintage Books, 1992)
What is the new economy? What is globalization? Is the euro the final seal on European Union? How is e-commerce transforming our world beyond economics? What is virtual money, and does it have real value? How do social concerns and societal ills (drugs, poverty, AIDS, endangered natural resources) play a part in the rapidly changing world economy? What are multinationals, and do they signal the end of nationalism? These and many other pertinent issues are addressed in an enlightening and entertaining handbook for those who want to be economically literate (and who doesn't?).